THE ANALYSIS OF THE PHARMACEUTICAL MARKET ON THE EXAMPLE OF MEDICINES OF GROUP OF INHIBITORS OF THE PROTON POMP - N. V. Mazova; A. L. Marchenko; N. V. Marchenko (Разработка и регистрация лекарственных средств, 2019)
In this research is carried out the review of the Russian pharmaceutical market and the comparative characteristic of medicines of group of inhibitors of a proton pomp. Data on production, registration and sales of this group of medicines are provided during 2007-2016.